2013
DOI: 10.1002/bate.201300059
|View full text |Cite
|
Sign up to set email alerts
|

Digitale Photogrammetrie in der Bautechnik

Abstract: Die digitale Nahbereichsphotogrammetrie ermöglicht die berührungslose Erfassung von Verformungen, Rissen und anderen Schädigungen bei experimentellen Untersuchungen von Baustoffen, Bauteilen und Baukonstruktionen. Bei Beton bzw. Stahlbeton sind die zu beobachtenden Dehnungen (ca. 3, 5 ‰ Druckbruchdehnung, ca. 0,1 ‰ Zugbruchdehnung) und Rissbreiten (ab 0,05 mm) im Vergleich zu anderen Materialien sehr klein. Bei Betonbauteilen wird die digitale Nahbereichsphotogrammetrie daher oft an der Leistungsgrenze betrieb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition, the measurement accuracy must also be taken into account for the comparison of both measurement methods. The accuracy of DIC measurements is described by the SD of the measured values . This is calculated by the deviation Δ ε of the measured values from the mean value curve (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the measurement accuracy must also be taken into account for the comparison of both measurement methods. The accuracy of DIC measurements is described by the SD of the measured values . This is calculated by the deviation Δ ε of the measured values from the mean value curve (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic tests were performed load‐controlled on five different test series (n° VC1, VC2, VC3, VC4, and VC5) with the same lower‐ and upper stress‐level but different loading rates as specified in Table . This procedure was chosen because the measurement noise of the DIC depends on the measuring rate, which has to be selected according to the loading rate . Measurement noise is a fluctuation of the results underlying any measurement system and defines the accuracy of the system.…”
Section: Experimental Programmentioning
confidence: 99%
“…In addition to the crack analysis, parameters such as pattern visibility, lighting effects, aperture, number of cameras, exposure time and exposure type affect the crack evaluation [3,11,22,23]. To quantify the impact of camera resolution on mechanical properties and multiple crack characteristics using DIC, Godek et al [16] conducted experiments on cementitious composites.…”
Section: Introductionmentioning
confidence: 99%
“…This research demonstrated that increased resolution results in finer pattern precision and led to a twofold increase in the number of detected cracks during the analysis. During the evaluation process of measurements using DIC, key parameters for evaluation include facet size, the quantity of images per measurement, the spacing between two facets (facet overlap), strain tensors' neighborhood, averaging spatially and temporally, and the threshold for the scaling factor based on the major strain [3,22]. However, it should be noted that the accuracy of image analysis is constrained by systematic and random errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation